Beyond a cure for TB: confronting the hidden burden of post-TB lung disease - Y. Kherabi; D.R. Silva; R. Centis; L. D’Ambrosio; G.B. Migliori (IJTLD Open)
Although much attention is given to diagnosis and treatment for TB, recent evidence highlights the suffering that occurs after patients are ‘cured’. This issue of IJTLD Open includes two studies that improve our understanding of the long-term impact of TB. First, a study in Kenya, Uganda, Zambia and Zimbabwe evaluated the feasibility of assessing and referring TB patients for comorbidities, risk factors and disabilities within national TB programmes. Second, a study of patients who successfully completed TB treatment in China sheds light on the long-term sequelae of TB. The combined findings reinforce the need to integrate care strategies into TB programmes to address these health challenges.